(untitled) (Praxis Educativa, 2012)
The present work is centered on the predominant place occupied by "classroom-teaching practices" in teacher training and development, on the cut-downs to which they are often subjected, on the "residual" character traditionally granted to them, and the technical perspective from which they are usually approached The result of a research project on beginning teachers being the starting point and the concept of educational ’know-how" being appealed to, an alternative is here proposed that involves a passage from academic formation to insertion into the educational job market which generates permanent training opportunities that allow educators to design and execute their own proposals. Thus, different teaching groups’ needs would be met in their uniqueness - needs that cannot be satisfied through the mere implementation of unifying or homogenizing’ teacher-development programmer. The research lines here developed are aimed at achieving that groups of educators analyze their own practices, that they reflect upon them and enrich the analyses with the inclusion of pertinent theoretical aspects in order to jointly detect problems and elaborate solutions. In this way, important contributions are made for continuous training and development to cease being a mere succession of diverse courses.